SAAP-148 Eradicates MRSA Persisters Within Mature Biofilm Models Simulating Prosthetic Joint Infection - Scheper, Henk; Wubbolts, Julia M.; Verhagen, Joanne A. M.; de Visser, Adriëtte W.; van der Wal, Robert J. P.; Visser, Leo G.; de Boer, Mark G. J.; Nibbering, Peter H. (Frontiers in Microbiology, 2021)
Prosthetic joint infection (PJI) is a severe complication of arthroplasty. Due to biofilm and persister formation current treatment strategies often fail. Therefore, innovative anti-biofilm and anti-persister agents are urgently needed. Antimicrobial peptides with their broad antibacterial activities may be such candidates. An in vitro model simulating PJI comprising of rifampicin/ciprofloxacin-exposed, mature methicillin-resistant Staphylococcus aureus (MRSA) biofilms on polystyrene plates, titanium/aluminium/niobium discs and prosthetic joint liners was developed. Bacteria obtained from and residing within these biofilms were exposed to SAAP-148, acyldepsipeptide-4, LL-37 and pexiganan. Microcalorimetry was used to monitor the heat flow by the bacteria in these models. Daily exposure of mature biofilms to rifampicin/ciprofloxacin for 3 days resulted in a 4-log reduction of MRSA. Prolonged antibiotic exposure did not further reduce bacterial counts. Microcalorimetry confirmed the low metabolic activity of these persisters. SAAP-148 and pexiganan, but not LL-37, eliminated the persisters while ADEP4 reduced the number of persisters. SAAP-148 further eradicated persisters within antibiotics-exposed, mature biofilms on the various surfaces. To conclude, antibiotic-exposed, mature MRSA biofilms on various surfaces have been developed as in vitro models for PJI. SAAP-148 is highly effective against persisters obtained from the biofilms as well as within these models. Antibiotics-exposed, mature biofilms on relevant surfaces can be instrumental in the search for novel treatment strategies to combat biofilm-associated infections.